Metody analizy i eksploracji danych - Nycz, Małgorzata; Smok, Barbara (The Data Analysis and Exploration Methods, 2005)
The paper has been devoted to the data warehouse exploration issues as a tool for realization multidimensional analysis as well as data mining. It consists of five parts. After short introduction, the idea of data warehouse has been described. The next part presents the warehouse methods that are especially useful in multidimensional analysis. Part four is devoted to data mining in warehouse. At the end short summary has been presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 50-61